Discursive Features of Russian as a Foreign Language Textbooks: Respond to Negative Russia Image Stereotypes - Svetlana Gerasimova; Natalia Kasyanova (ARPHA Proceedings, 2021)
The article analyses the didactic space of the Russian as a foreign language textbooks and manuals within the pedagogical discourse in terms of intercultural communication theory. It discloses the influence of national stereotypes on the image of Russia in the foreigners as a sketchy primitive idea on this social phenomenon formed during certain period of time. The paper highlights the necessity of altering the vector of stereotypes issues research taking into account their design properties and functions, in order to boost intercultural communication. The research characterizes the understanding and implementation of intercultural approach by the authors of contemporary Russian as a foreign language textbooks. It focuses on discursive strategies and tactics of establishing intercultural communication. Strategic component promotes didactic communication, when Russian as foreign language textbooks didactic space acquires associative, dialogue and polyphonic nature. The paper reveals positive and attractive for the foreign contacts Russia image within the analyzed textbooks and manuals. It elicits discursive features of Russian as a foreign language textbooks as a soft power tool that contributes to leveling negative (stereotypical) image of Russia and establishing the dialogue of cultures. The authors prove the process of teaching Russian as a foreign language to be based on essential support of the Russian language as a powerful resource of consolidating forces that strengthen the fundamental positions of the Russian Federation in the new geopolitical space.